The Accession of James I
XXVII, 215 p.
Keywords: This book analyzes the consequences of the accession of James I in 1603 for English and British history, politics, literature and culture. Questioning the extent to which 1603 marked a radical break with the past, the book explores the Scottish, Welsh, and wider European and colonial contexts, to this crucial date in history.